2001
DOI: 10.1111/j.1527-3466.2001.tb00061.x
|View full text |Cite
|
Sign up to set email alerts
|

Carvedilol: Molecular and Cellular Basis for Its Multifaceted Therapeutic Potential

Abstract: Carvedilol is a unique cardiovascular drug of multifaceted therapeutic potential. Its major molecular targets recognized to date are membrane adrenoceptors (â 1 , â 2 , and á 1 ), reactive oxygen species, and ion channels (K + and Ca 2+ ). Carvedilol provides prominent hemodynamic benefits mainly through a balanced adrenoceptor blockade, which causes a reduction in cardiac work in association with peripheral vasodilation. This drug assures remarkable cardiovascular protection through its antiproliferative/athe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
57
0
4

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(62 citation statements)
references
References 116 publications
1
57
0
4
Order By: Relevance
“…Carvedilol, both the beta blocker (β1, β2) and alpha blocker (α1), is indicated in the management of congestive HF. It is used as an adjunct to conventional treatments with its effect probably mediated through the potent antioxidant and anti-apoptotic activities [42] . The Japanese Diastolic Heart Failure Study has recently suggested the beneficial effects of standard dose prescriptions of carvedilol (> 7.5 mg/d) in HF without affecting …”
Section: Of Mitochondria In the Cardiomyocytesmentioning
confidence: 99%
“…Carvedilol, both the beta blocker (β1, β2) and alpha blocker (α1), is indicated in the management of congestive HF. It is used as an adjunct to conventional treatments with its effect probably mediated through the potent antioxidant and anti-apoptotic activities [42] . The Japanese Diastolic Heart Failure Study has recently suggested the beneficial effects of standard dose prescriptions of carvedilol (> 7.5 mg/d) in HF without affecting …”
Section: Of Mitochondria In the Cardiomyocytesmentioning
confidence: 99%
“…It is a non selective blocker of α1 and β-adrenergic receptors, while displaying vasodilating properties has potent antioxidant and antiapoptotic properties [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…16,31,32 Carvedilol also has negative inotropic and chronotropic actions, as well as potent vasodilation, antiischemic, antiapoptotic and antioxidant effects. 33 Given that mechanical stressinduced apoptosis does not explain lamin A/C-related DCM, it seems likely that the hemodynamic and antiapoptotic benefits of exercise and carvedilol are relatively less important than other direct myocardial effects. Antioxidant actions of exercise and carvedilol are of particular interest in view of recent data implicating oxidative stress in heart failure and in other laminopathy phenotypes, including lipodystrophy, premature ageing, and amyotrophic quadricipital syndrome with cardiac involvement.…”
mentioning
confidence: 99%